Online closed‐loop real‐time tES‐fMRI for brain modulation: A technical report. Issue 10 (22nd September 2022) - Mulyana, Beni; Tsuchiyagaito, Aki; Misaki, Masaya; Kuplicki, Rayus; Smith, Jared; Soleimani, Ghazaleh; Rashedi, Ashkan; Shereen, Duke; Bergman, Til Ole; Cheng, Samuel; Paulus, Martin P.; Bodurka, Jerzy; et al.
Abstract: Recent studies suggest that transcranial electrical stimulation (tES) can be performed during functional magnetic resonance imaging (fMRI). The novel approach of using concurrent tES‐fMRI to modulate and measure targeted brain activity/connectivity may provide unique insights into the causal interactions between the brain neural responses and psychiatric/neurologic signs and symptoms, and importantly, guide the development of new treatments. However, tES stimulation parameters to optimally influence the underlying brain activity may vary with respect to phase difference, frequency, intensity, and electrode's montage among individuals. Here, we propose a protocol for closed‐loop tES‐fMRI to optimize the frequency and phase difference of alternating current stimulation (tACS) for two nodes (frontal and parietal regions) in individual participants. We carefully considered the challenges in an online optimization of tES parameters with concurrent fMRI, specifically in its safety, artifact in fMRI image quality, online evaluation of the tES effect, and parameter optimization method, and we designed the protocol to run an effective study to enhance frontoparietal connectivity and working memory performance with the optimized tACS using closed‐loop tES‐fMRI. We provide technical details of the protocol, including electrode types, electrolytes, electrode montages, concurrent tES‐fMRI hardware, online fMRI processing pipelines, and the optimization algorithm. We confirmed the implementation of this protocol worked successfully with a pilot experiment. Abstract : Here, we assessed tolerability/safety/noise concerns and methodological aspects of a real‐time closed‐loop tACS‐fMRI trial. We discussed the risk of electrode heating and localization of the electrodes, while people are lying down inside the scanner, MRI conditional stimulator setup, RF filters, and wire outing patterns, the amount/type of contact medium, the timing of concurrent tACS within the fMRI paradigm, optimization algorithm and parameters search space to optimally target the frontoparietal network. The initial results of feasibility and applicability of closed‐loop tACS‐fMRI are reported, and potential hypotheses for the outcomes are summarized.